1981
DOI: 10.1037/0096-1523.7.6.1186
|View full text |Cite
|
Sign up to set email alerts
|

Detection of symmetry.

Abstract: The time to detect symmetries in square field patterns was measured. The same relationships among mean detection times for different symmetries was found in both well-practiced and naive subjects. When the task was to detect any symmetry, detection times were faster for multiply symmetry was faster than diagonal, singly symmetric ones. Horizontal-vertical symmetry was faster than diagonal, which was faster than centric. When the task was to detect specific symmetry, that is, vertical, horizontal,diagonal, or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
153
1
1

Year Published

1985
1985
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(175 citation statements)
references
References 27 publications
20
153
1
1
Order By: Relevance
“…However, not all symmetries are equal. A substantial number of studies have found that symmetry along a vertical axis is more advantageous than symmetry along other axes (e.g., Kahn & Foster, 1986;Palmer & Hemenway, 1978;Royer, 1981). However, symmetry along the horizontal axis has also been found to be stronger than symmetry along oblique angles (e.g., Fisher & Bornstein, 1982).…”
Section: Symmetrymentioning
confidence: 99%
“…However, not all symmetries are equal. A substantial number of studies have found that symmetry along a vertical axis is more advantageous than symmetry along other axes (e.g., Kahn & Foster, 1986;Palmer & Hemenway, 1978;Royer, 1981). However, symmetry along the horizontal axis has also been found to be stronger than symmetry along oblique angles (e.g., Fisher & Bornstein, 1982).…”
Section: Symmetrymentioning
confidence: 99%
“…Regardless of the true nature of the mechanisms that underlie the effects we have reported, they suggest that direction of motion could be a potent factor in other "reference frame" phenomena (see Palmer, 1983)-for example, shape constancy and its failure in memory for disoriented figures (Rock, 1973;Wiser, 1981), shape discrimination between squares and diamonds (Palmer, 1985), symmetry detection in figures at different orientations (Palmer & Hemenway, 1978;Royer, 1981), and perhaps even the perceived organization of complex motion events (Johansson, 1950). These are merely conjectures at present, of course, but if the line of reasoning followed here is correct, such effects should be found for suitably constructed stimuli.…”
Section: Moving Triangles 235mentioning
confidence: 99%
“…The advantage of symmetrical forms is due to the reduction in information from redundant features. Royer (1981) also gave a two-process explanation. Symmetry is encoded integrally with the features of the object, but in detection or decoding tasks, the observer also has to perform a serial hierarchical decomposition of the code.…”
mentioning
confidence: 98%
“…Correspondence concerning this article should be addressed to S. Ballesteros, Departamento de Psicologia Basica II, Ciudad Universitaria SfN, Universidad Nacional de Educacion a Distancia, 28040 Madrid, Spain (e-mail: sballest@cu.uned.es)ortoS.Millar.Department of Experimental Psychology, University ofOxford, South Parks Road, Oxford OXI 3UD, England (e-mail: susanna.millar@psy.ox.ac.uk). Locher & Nodine, 1973;Mach, 1897;Palmer, 1989;Rock, 1983;Royer, 1981). Bilateral mirror-image symmetry about the vertical axis has usually been reported as being more salient than is symmetry about horizontal or oblique axes (Barlow & Reeves, 1979;Corballis & Roldan, 1975;Fisher & Bomstein, 1982;Munsinger & Forsman, 1966;Palmer, 1991;Palmer & Hemenway, 1978;Royer, 1981;Wagemans, Van Gool, & d'YdewalIe, 1992).…”
mentioning
confidence: 99%
See 1 more Smart Citation